PHD Defence: â€œComment Spaceâ€ by Geoffrey Glass - Phan, Vu Thuy Anh (Stream: Interdisciplinary Journal of Communication, 2015)
Our dear colleague, Geoffrey Glass, will defend his PHD dissertation on Wednesday, November 18th, 2015 at Harbour Centre, Room 1520 (10:00 am- 1:00 pm). Here is the abstract of his dissertation “Comment Space”.